UNDERSTANDING THE TRAVELERS’ INTENTION TOWARDS VIRTUAL TOURISM ADOPTION USING VALUE-BASED ADOPTION MODEL - Kelvin Lim; Siti Nor Bayaah Ahmad; Nor Asiah Mahmod; Irma Wani Othman; Suddin Lada, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Virtual Tourism (VT) is defined as a novel concept that enables potential tourists to enjoy tourist sites without visiting them physically. Nonetheless, VT remains a novelty for Malaysian tourists. Therefore, this study intends to ascertain travellers’ adoption intentions in Virtual Tourism via the use of a Value-based Adoption Model (VAM). Travellers in Malaysia aged 21 to 39 were the analytic unit in this study. A total of 302 usable responses were obtained from an online self-administered questionnaire and analysed using Partial Least Squares-SEM in conjunction with the SmartPLS programme.